A Review Of Literature On The Effectiveness Of Vojta Therapy On Balance In Children With Spastic Cerebral Palsy (International Journal of Research in Pharmacology & Pharmacotherapeutics, 2025)
Background: Cerebral palsy (CP) is a group of neurological disorders that affect movement and muscle coordination, with spasticity being one of the most common forms. Children with spastic CP often face significant challenges with balance, motor function, and postural control, which can severely impact their quality of life. Traditional rehabilitation therapies, such as physiotherapy, occupational therapy, and pharmacological interventions, are typically used to manage symptoms. However, the effectiveness of these treatments can vary, and many children still struggle with balance and coordination.Methodology: Articles were sourced from reputable databases including PubMed and Google Scholar, spanning 2011 to 2023. The review included systematic reviews, randomized controlled trials, and single-blinded experimental studies examining the impact of Vojta Therapy on balance in children with spastic cerebral palsy.Result: The review identified 17 relevant articles, of which 13 met the inclusion criteria and were subjected to full-text analysis. The findings indicate that Vojta therapy significantly improves motor function, balance, and overall quality of life in individuals with cerebral palsyConclusion: Vojta therapy shows potential as an effective therapeutic intervention for improving balance and motor function in children with spastic cerebral palsy. The therapy, by stimulating reflex locomotion patterns, appears to facilitate neuroplasticity, enhancing postural control and coordination in these children.